An Energetic Framework for Human Psychodynamics: Modeling the Interplay of Behavior, Emotion, and Homeostatic Balance - Devi, Oinam Shantibala (Journal of Progress in Civil Engineering, 2026)
Energy, in its various forms, plays a crucial role in both the physical world and in the realm of human emotions and behaviour. Energy, whether physical or emotional, is a powerful force that can be harnessed and directed in various ways. Understanding its different forms and learning to manage and channel it effectively can lead to a more balanced, productive and fulfilling life with peace of mind. Here are some key aspects of energy: